Determination of Areas with Solar Power Plant Installation Potential in Kars Province by Using GIS Analysis and AHP Method - Mucip Demir (Coğrafya Dergisi)
Determining where to install solar panels and power plants is a very complex and difficult to analyze spatial decision-making problem series. In order to solve this series of problems, Multi-Criteria Decision-Making methods integrated into Geographic Information Systems software have been preferred in recent years. This study aims to determine the areas with solar energy production potential in the Kars province. In the research, thematic maps were created for the purpose of processed research by obtaining data from various open sources in order to analyze the determined criteria that affect the location selection of areas with solar energy production potential. Based on the criteria weights calculated by AHP analysis from these maps, suitable areas with potential for solar power plant installation in the province of Kars were mapped in the GIS environment. As a result of the research, an area of 54,581 km2, which is very suitable and suitable for solar power plant installation in Kars province, has been determined and these lands constitute 55 % of the province’s surface area with a total surface area of 10,193 km2. The lands with potential for solar power plant installation in the Kars province show a homogeneous distribution.